Pengaruh Social Media Influencers terhadap Brand Image dan Purchase Intention pada Produk Scarlett Whitening - Cornellius Raditya Bagaskoro; Yuliasti Ika Handayani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to examine the influence of social media influencers on purchase intention and the role of brand image as a mediator for Scarlett brand beauty products. This research is a quantitative study involving 196 respondents as the research sample, with data collected through an online survey. Data analysis was performed using Structural Equation Modelling (SEM) software with the SmartPLS 3.0 program. The results obtained in this study indicate that social media influencers have a significant impact on purchase intention, whereas brand image does not have a significant impact on purchase intention. Brand image significantly mediates the influence of social media influencers on purchase intention. The fact that brand image does not have a significant influence on purchase intention suggests that other factors, such as price, product quality, promotion, and recommendations from others, remain more dominant in influencing consumer purchase intentions. This study provides additional information on the influence of social media influencers on purchase intention with brand image mediation for Scarlett products. Practical suggestions and recommendations for further research are also presented in the final section.